2007
DOI: 10.1590/s1415-47572007000300012
|View full text |Cite
|
Sign up to set email alerts
|

Associations of MYF5 gene polymorphisms with meat quality traits in different domestic pig (Sus scrofa) populations

Abstract: The MYF5 gene is first inducibly expressed in muscle cell during embryonic muscle development and plays an important role in regulating the differentiation of skeletal muscle precursors. In this study we used PCR-RFLP to investigate two pig (Sus scrofa) populations (n = 302) for two MYF5 gene polymorphisms, a previously unreported novel Met-Leu shift single nucleotide polymorphism (SNP) MYF5/Hsp92II located on exon 1 and the previously identified intron 1 MYF5/HinfI SNP. Haplotype and association analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
(21 reference statements)
2
4
0
Order By: Relevance
“…The association results between g.1911A NG SNP genotypes of MYF5 gene and growth traits are consistent with previous investigations that this polymorphism had significant association with average daily gain (ADG) in Canadian beef cattle (Li et al, 2004); ADG and yearling weight in Hanwoo (Chung and Kim, 2005) and growth related traits in Chinese cattle (Zhang et al, 2007). Several investigations have been focused on the detection of polymorphisms in MYF5 gene in pig and revealed significant association with production and meat quality traits (Liu et al, 2007;Carmo et al, 2005). However, no relationships with production traits in pigs have also been reported by Verner et al (2007).…”
Section: Discussionsupporting
confidence: 90%
“…The association results between g.1911A NG SNP genotypes of MYF5 gene and growth traits are consistent with previous investigations that this polymorphism had significant association with average daily gain (ADG) in Canadian beef cattle (Li et al, 2004); ADG and yearling weight in Hanwoo (Chung and Kim, 2005) and growth related traits in Chinese cattle (Zhang et al, 2007). Several investigations have been focused on the detection of polymorphisms in MYF5 gene in pig and revealed significant association with production and meat quality traits (Liu et al, 2007;Carmo et al, 2005). However, no relationships with production traits in pigs have also been reported by Verner et al (2007).…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, inverted repeat sequences have been reported to be associated with the breakpoints during gene conversion events [4]. The polymorphisms in the porcine MYF5 gene observed in this study have not been reported previously and there is greater diversity than previously reported [6,18]. These results confirmed that PCR-SSCP is a simple and sensitive means of detecting DNA polymorphisms in the MYF5 gene.…”
Section: Resultssupporting
confidence: 88%
“…Two alleles have been reported at exon 1 [6], exon 2 [19] and exon 3 [18]. Although PCR-RFLP analysis is a simple method for screening DNA polymorphism, it is limited by the fact that variation in genes can only be detected in the restriction endonuclease recognition sequences and then only if it changes the cleavage pattern of the restriction endonuclease.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle regulatory factor ( MRF ) gene family, which encoded a basic helix-loop helix protein and was responsible for myotubular transformation. Two genes, Myf5 and Myf6 , in MRF family were found to regulate the development of skeletal muscle fibers and postnatal growth hypertrophy, which affected meat quality [ 118 , 119 , 120 ].…”
Section: Application Of Trait Selection In Farm Animals By Using Smentioning
confidence: 99%